The Prevalence of Atrophic Tongue in Patients Referring to Isfahan Health Clinics - roya hashemi; homeyra mardani; mahdi mohammadi (Kerman University of Medical Sciences, 2016)
The Prevalence of Atrophic Tongue in Patients Referring to Isfahan Health Clinics  Mardani Homyra1, Hashimi Roya2*, Mohamadi Mehdi3 Received: 05. 11. 2015             Revised: 29. 02. 2016              Accepted: 08. 03. 2016 1. Assistant Professor, Department of Oral and Maxillofacial, School of Dentistry, Islamic Azad University Khorasgan, Isfahan, Iran. 2. Resident, Department of Orthodontics, Qazvin University of Medical Sciences, Qazvin, Iran. 3. Associate Professor, Health Promotion Research Center, Zahedan University of Medical Sciences, Zahedan, Iran. *Correspondence: Department of Orthodontics, School of Dentistry, BahonarBlv. Qazvin, Iran. Tel: 09134034886             Email: roya.3816@yahoo.com Abstract Introduction:Atrophic tongue or smooth tongue is resulted from atrophy of the filiform papillae. The tongue often shows a shiny red appearance. This lesion may be seen in many systemic diseases. Method:This descriptive analytic study was conducted on 200 patients referred to Isfahan health clinics in spring 2015. A questionnaire about demographic characteristics and history of mouth diseases was filled out for each patient and they were clinically examined afterwards. If the atrophic tongue was observed, a sample was taken by swab from the site of the lesion to assess fungal infection. For positive fungal cultures, Candida species were detected using germ tube method. Data were analyzed using χ2 and binomial test and through SPSS15. Results:Of the studied patients, 174 ones had systemic diseases and 26 patients (13%) had atrophic tongue. Candida was found in 73.1% of the lesions. Germ Tube detected 57.9% Candida Albicans and 42.1% Candida Glabrata. Atrophic tongue showed no significant association with dry mouth, burning sensation of tongue, age and gender. Conclusion:This study showed a significant prevalence of atrophic tongue in patients with systemic diseases. Therefore, systemic diseases should be controlled and treated. There is high chance of detecting Candida in atrophic tongue with equal chance of detecting Candida Albicans and Candida Glabrata in this lesion. Keywords:Prevalence, Atrophic tongue, Systemic diseases, Health Clinics Citation:Mardani H, Hashimi R, Mohamadi M. The Prevalence of Atrophic Tongue in Patients Referring to Isfahan Health Clinics in 2015. Journal of Health Based Research 2016; 1(3): 267-276.